Death or Damnation: Surrogacy and Religious Beliefs. (August 2019) - Baumrucker, Steven J.; Stolick, Matt; Hutchinson, Laura; Eastridge, Angela; Devereux, Lawrence; Adkins, Russell W.; Carter, Gregory T.
MC is a 42-year-old female who was in a motor vehicle accident and suffered multiple contusions as well as a fracture of the left femur, pelvic ramus, and left orbit. Due to contusion of the brain, MC has been comatose for over a week and is on mechanical ventilation to protect her airway. There is no written declaration of surrogacy. During the admission, surgery to repair the left femoral fracture was performed and was complicated by severe blood loss. Currently, MC's hematocrit is 24% with a hemoglobin of 7.4. The trauma team asserts that a blood transfusion would be in MC's best interests. Since MC lacks capacity for decision making, she cannot consent to blood transfusion. Her parents are Jehovah's Witnesses and refuse to approve blood transfusion, stating that it is against their faith. MC's brother, however, states that MC is not a practicing Jehovah's Witness and wants the medical team to provide the blood transfusion. The parents insist that decision making is their right; MC's brother feels he should be making decisions. The trauma teams calls for an emergency consultation with the hospital ethics committee.